Skewed X‐chromosome inactivation plays a crucial role in the onset of symptoms in carriers of Becker muscular dystrophy. (April 2017) - Viggiano, Emanuela; Picillo, Esther; Ergoli, Manuela; Cirillo, Alessandra; Del Gaudio, Stefania; Politano, Luisa
Abstract: Background: Becker muscular dystrophy (BMD) is an X‐linked recessive disorder affecting approximately 1: 18.000 male births. Female carriers are usually asymptomatic, although 2.5–18% may present muscle or heart symptoms. In the present study, the role of the X chromosome inactivation (XCI) on the onset of symptoms in BMD carriers was analysed and compared with the pattern observed in Duchenne muscular dystrophy (DMD) carriers. Methods: XCI was determined on the lymphocytes of 36 BMD carriers (both symptomatic and not symptomatic) from 11 families requiring genetic advice at the Cardiomyology and Medical Genetics of the Second University of Naples, using the AR methylation‐based assay. Carriers were subdivided into two groups, according to age above or below 50 years. Seven females from the same families known as noncarriers were used as controls. A Student's t ‐test for nonpaired data was performed to evaluate the differences observed in the XCI values between asymptomatic and symptomatic carriers, and carriers aged above or below 50 years. A Pearson correlation test was used to evaluate the inheritance of the XCI pattern in 19 mother–daughter pairs. Results: The results showed that symptomatic BMD carriers had a skewed XCI with a preferential inactivation of the X chromosome carrying the normal allele, whereas the asymptomatic carriers and controls showed a random XCI. No concordance concerning the XCI pattern was observed between mothers and related daughters. Conclusions: The data obtained in the present study suggest that the onset of symptoms in BMD carriers is related to a skewed XCI, as observed in DMD carriers. Furthermore, they showed no concordance in the XCI pattern inheritance.